ANALISA PERILAKU CYBERBULLYING PADA REMAJA PEREMPUAN DI JEJARING SOSIAL INSTAGRAM Analyis of Cyberbullying Behavior in Teenage Girls On Instagram Social Network - Fauziah Yanis (PRoMEDIA, 2022)
Cyberbullying is the behavior of an act of intimidation that occurs in cyberspace, especially on social media. Cyberbullying is often carried out by the surrounding community, especially teenagers who are currently very close to technological advances. This cyberbullying phenomenon often appears on social media networks because of the increasingly advanced use of internet technology in accessing social media. This study focuses on the Analysis of Cyberbullying Behavior in Adolescent Girls on the Instagram Social Network which is carried out by a group of teenage girls through the Instagram social network. The purpose of this research is to find out how the behavior of the perpetrator to the victim. The theory in this study is to use the theory of communication psychology and social media. The researcher used a qualitative descriptive method with a phenomenological approach using data collection techniques with observation, interviews and in-depth documentation techniques with sources and using data validity techniques, namely triangulation of data sources. The results of this study show that the perpetrators treat cyberbullying through Instagram, where the perpetrator comments on every post uploaded by the victim, the comments are more directed towards body shaming and frontal comments.Keywords: social media, cyberbullying, adolescent girls.